A study assessing the knowledge, attitude, and practices of parents regarding childhood hypopigmented lesions - Akila Ravindra; Veranna Shastry; Chetana Prakash; Jaydev Betkerur (Wolters Kluwer Medknow Publications, 2019)
Background: Pigmentary disorders are believed to be the most common group of dermatoses in the pediatric age group. Loss of pigment can have a profound psychological impact on parents of the affected child. There are few studies available in India about the evaluation of hypopigmented lesions in the pediatric age group. Objectives: The objective of this study was conducted to assess the knowledge and attitude and various practices of parents toward hypopigmented disorders. Materials and Methods: A total of 130 pediatric patients were evaluated for hypopigmented lesions. Parent of each child was given a preformed questionnaire for the assessment of knowledge and attitude and various practices of their skin condition. Results: The frequency of hypopigmentary disorders among children was 3.28/1000. The mean age was 8.41 years. Nearly 9.33% of patients had onset at birth. In the study of 130 parents, 82 had low, 32 had moderate, and 14 had high knowledge levels, and 84 had unfavorable, and 46 had favorable attitudes. The parents, who had incorrect practices, were 53% and 35.67% had correct practices. Conclusion: The most common hypopigmentary conditions are benign and self-limiting, which requires proper counseling of the parents. A good knowledge and attitude will not only liberate them from traditional beliefs and home remedies that have been used in most of the Indian households but will also make them understand the magnitude of the problem their child could face if they do not seek proper advice from a doctor at the right time.